Thermal sensation and percentage of dissatisfied in thermal environments with positive and negative vertical air temperature differences - Yuxin Wu; Sheng Zhang; Hong Liu; Yong Cheng (Energy and Built Environment, 2023)
Considering the percentage of dissatisfied due to local thermal sensation (PDLTSV), a vertical air temperature difference (ΔTd) threshold of about 3 °C was recommended in standards. However, some novel air distribution methods might create large positive (which means the head warmer than the feet, vice versa) or negative ΔTd, with no suitable proved criteria to be used. In this study, sixteen subjects were seated in a climatic box placed in a climate chamber to evaluate thermal sensation and percentage of dissatisfied with negative and positive ΔTd in different whole-body thermal conditions. Air temperatures were controlled independently at the upper and lower body parts, with 13 different air temperature sets combined with 22 °C, 25 °C, 28 °C, and 31 °C (i.e. -9 °C ≤ ΔTd ≤ 9 °C). Results showed that subjects were more thermally sensitive at the upper body and with positive ΔTd than at the lower body or with negative ΔTd. The 80% acceptable ΔTd range is about -8 to 7 °C in overall neutral (TSV = 0), -7 °C to 6 °C in slightly cool (TSV = -0.5) conditions, which is wider than -3 to 3 °C in slightly warm conditions (TSV = +0.5). By considering the factors of both TSV and ΔTd, a new overall percentage of dissatisfied index (OPDP) was proposed. Case studies show that the new OPDP index is more precise and suitable for the evaluations of different air distributions to predict overall percentage of dissatisfied in thermal environments with vertical air temperature difference.